Sensitive Spectrophotometric Methods for the Determination of Ascorbic Acid - H. D. Revanasiddappa; M. A. Veena (E-Journal of Chemistry)
Two simple and sensitive spectrophotometric methods (A and B) have been described for the determination of ascorbic acid. Method A is based on the oxidation of ascorbic acid (AA) by known excess of Se(IV) in hydrochloric acid medium and subsequent determination of unreacted Se(IV) by reacting it with iodide in the same acid medium to liberate iodine, which react with starch to form a stable blue coloured iodine-starch complex, which shows maximum absorbance at 590 nm. Method B is based on the oxidation of ascorbic acid (AA) by known excess of Cr(VI) in sulphuric acid medium and the determination of unreacted Cr(VI) with diphenyl carbazide (DPC) under the same acidic medium to produce a stable red-violet coloured species, which shows a maximum absorbance at 550 nm. The reacted oxidants (in methods A and B) correspond to the AA content. The apparent molar absorptivity values are found to be 1.627×104 and 1.641×104 L mol-1 cm-1 for methods A and B, respectively. The proposed methods are simple, sensitive and suitable for the routine analysis of AA in pharmaceutical formulations and in real samples.